GRADE DECISION-MAKING AND GRADE INFLATION BY EFL SECONDARY SCHOOL TEACHERS AND THEIR MORAL JUSTIFICATIONS IN ONLINE LEARNING DURING THE PANDEMIC - Romadhon, - (2023)
This study investigated what grade decision-making factors EFL secondary school teachers considered in online learning during the pandemic and how they provided measurable and observable evidence in their assessment. Also, this study identified EFL secondary school teachers' considerations in grade decision-making that lead to grade inflation and how they morally justified it during emergency remote teaching. The study used the framework of grade factors: internal (Cheng & Sun, 2015) and external factors (Cheng & Sun, 2015; Brown & Abeywickrama, 2010; McMillan & Nash, 2000), students' academic and non-academic records (Lawrence, Rober, Cross, & Frary, 1996; McMillan, Myran, & Workman, 2002), cognitive and non-cognitive performances (Arrafii, 2020; Brookhart, 2016), or product and process factors (Guskey & Link, 2019). An explanatory sequential mixed-methods design was conducted to collect, analyze and interpret data sequentially from a questionnaire as quantitative data to interviews and document analysis as qualitative data. The findings present that EFL secondary school teachers conducted a hodgepodge grading, a combination of all grade factors mentioned above that potentially led to grade inflation. Although EFL secondary school teachers provided measurable and observable evidence in their assessment, their grade decision-making was still identified as grade inflation based on several theories. Grade inflation by EFL secondary school teachers was morally justified because they still upheld values in classroom assessment. This study gives theoretical, practical, and policy significance to English teachers, schools, and the government regarding assessment standards and language testing and evaluation. Eventually, this gives evaluations and recommendations for stakeholders, experts, and educators for assessment standards in both face-to-face and online settings. Keywords: EFL teachers, grade decision-making, grade inflation, Indonesian secondary schools, online language teaching during the pandemic